Odpowiedź:
[tex]sin\alpha=\frac{H}l\\H=lsin\alpha\\l=\frac{H}{sin\alpha}\\S=\frac{2rH}2\\S=rH\\S=rlsin\alpha\\r=\frac{S}{lsin\alpha}[/tex]
a)
[tex]Pb=\pi rl\\Pb=\pi*\frac{S}{lsin\alpha}l\\Pb=\pi*\frac{Sl}{lsin\alpha}\\Pb=\pi*\frac{S}{sin\alpha}\\Pb=\frac{\pi S}{sin\alpha}\\\\V=\frac13Pp*H\\Pp=\pi r^2\\Pp=\pi*(\frac{S}{lsin\alpha})^2\\\\V=\frac{\pi*(\frac{S}{lsin\alpha})^2*lsin\alpha}{3}\\V=\frac{\pi*\frac{S^2}{lsin\alpha}}{3}\\V=(\pi*\frac{S^2}{lsin\alpha})*\frac13\\V=\frac\pi3*\frac{S^2}{3lsin\alpha}[/tex]
b)
[tex]S = 6\\\alpha = 50\\sin\alpha=0,766\\\\r=\frac{6}{0,766l\\}\\Pp=\pi*(\frac{6}{0,766l})^2\\Pp=\pi*\frac{36}{0,586756l^2}\\Pp=\frac{36\pi}{0,586756l^2}[/tex]
[tex]l=\frac{H}{0,766}\\l^2=\frac{H^2}{0,586756}\\Pp=\frac{36\pi}{0,586756*\frac{H}{0,586756}}\\Pp=\frac{36\pi}H[/tex]
[tex]V=\frac13Pp*H\\V=\frac13*\frac{36\pi}H*H\\V=\frac13*36\pi\\V=12\pi\\V=12*3,14=37.68=37.7j^3[/tex]
[tex]Pb=\frac{6\pi}{0,766}\\Pb=7.83\pi\\Pb=7,83*3,14=24.5862=24.6j^2[/tex]
Mam nadzieje ze dobrze :)